A Brief Review of Verbesina crocata (Cav.) Less., a Scantly Studied Medicinal Plant - Ivo Heyerdahl-Viau; Francisco López-Naranjo; Rebeca Córdova-Moreno; Ariana Urbina-Pastrana; Juan Manuel Martínez-Núñez* (Iranian Society of Pharmacognosy, 2023)
Although Verbesina crocata (Cav.) Less. is commonly used in Mexico as a medicinal plant to treat numerous disorders (a tradition dating back to pre-Hispanic times), scant scientific evidence exists on its pharmacological activity. The current review compiles information on the botanical characteristics, traditional medicinal use, and scientific evidence of the pharmacological effects of V. crocata with the aim of orienting future research. This narrative review searched for information on V. crocata with the key words "Verbesina crocata" and its local name "Capitaneja" from the following databases: PubMed, Scopus, EBSCO, SciELO, ScienceDirect, and Google Scholar. Few studies were found about the therapeutic effects of V. crocata in experimental animal models. Empirical knowledge of the effects of preparations predominated over scientific evidence. Among the diverse medicinal applications of V. crocata in Mexico, only its wound healing, antidiabetic, and diuretic activity have been tested scientifically. Little is known about the active constituents of the plant and less about their mechanisms of action or toxicity. Terpenes/steroids, glycosides, alkaloids, coumarins, quinones, saponins, and tannins have been identified as potentially responsible for therapeutic effects. The information available on V. crocata is predominantly empirical. The few scientific reports on its biological activity have confirmed the efficacy of the plant as a wound healing agent, antidiabetic, and diuretic. It is necessary to properly characterize the active principles and carry out evaluations of their mechanisms of action and toxicity.